2022
DOI: 10.1097/scs.0000000000008662
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Facial Proportionality, Attractiveness, and Character Traits

Abstract: Background: Facial proportionality and symmetry are positively associated with perceived levels of facial attractiveness. Objective: The aims of this study were to confirm and extend the association of proportionality with perceived levels of attractiveness and character traits and determine differences in attractiveness and character ratings between "anomalous" and "typical" faces using a large dataset. Methods: Ratings of 597 unique individuals from the Chicago Face Database were used. A formula was develope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…3 In addition, we found that increased representation of the middle one-third of the face was associated with higher ratings of attractiveness, trustworthiness, and femininity. 3 These results may indeed substantiate female hairline augmentation as the most efficacious change in facial anatomy for mitigating aesthetic concerns with "long face morphology," 1 although we recognize that cross-cultural differences may exist when making character inferences based on facial morphology.We were hoping the authors could comment on future directions for their investigation. Have the authors considered correlating changes in vertical anatomic measurements with patient and surgeon satisfaction ratings?…”
mentioning
confidence: 69%
“…3 In addition, we found that increased representation of the middle one-third of the face was associated with higher ratings of attractiveness, trustworthiness, and femininity. 3 These results may indeed substantiate female hairline augmentation as the most efficacious change in facial anatomy for mitigating aesthetic concerns with "long face morphology," 1 although we recognize that cross-cultural differences may exist when making character inferences based on facial morphology.We were hoping the authors could comment on future directions for their investigation. Have the authors considered correlating changes in vertical anatomic measurements with patient and surgeon satisfaction ratings?…”
mentioning
confidence: 69%
“…Eye-tracking is one such mechanism of objectively characterizing craniofacial anatomy, 35 in addition to other mechanisms including crowdsourcing 36,37 and soft tissue analysis. 38 However, visual attention data have not been studied alongside tests evaluating biases or social dispositions and may provide additional insight into the perception of those with facial anomalies. The purpose of this study was to evaluate whether interactions between biases and social characteristics with preoperative or postoperative status influence visual attention in laypeople toward those with facial anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Gaze patterns and visual attention have previously been used to study laypeople's perceptions of craniofacial anomalies. Eye-tracking is one such mechanism of objectively characterizing craniofacial anatomy, 35 in addition to other mechanisms including crowdsourcing 36,37 and soft tissue analysis 38 . However, visual attention data have not been studied alongside tests evaluating biases or social dispositions and may provide additional insight into the perception of those with facial anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Ratios adapted from previous studies [16][17][18] were used to characterize relative representation of facial features, where higher ratio scores indicated increased facial feature representation. For example: nasal width ratio ¼ interalar width face width  100…”
Section: Facial Ratiosmentioning
confidence: 99%